Physico-Chemical and In Vitro Characterization of Chitosan-Based Microspheres Intended for Nasal Administration - Csilla Bartos; Patrícia Varga; Piroska Szabó-Révész; Rita Ambrus (MDPI AG, 2021)
The absorption of non-steroidal anti-inflammatory drugs (NSAIDs) through the nasal epithelium offers an innovative opportunity in the field of pain therapy. Thanks to the bonding of chitosan to the nasal mucosa and its permeability-enhancing effect, it is an excellent choice to formulate microspheres for the increase of drug bioavailability. The aim of our work includes the preparation of spray-dried cross-linked and non-cross-linked chitosan-based drug delivery systems for intranasal application, the optimization of spray-drying process parameters (inlet air temperature, pump rate), and the composition of samples. Cross-linked products were prepared by using different amounts of sodium tripolyphosphate. On top of these, the micrometric properties, the structural characteristics, the in vitro drug release, and the in vitro permeability of the products were studied. Spray-drying resulted in micronized chitosan particles (2-4 μm) regardless of the process parameters. The meloxicam (MEL)-containing microspheres showed nearly spherical habit, while MEL was present in a molecularly dispersed state. The highest dissolved (>90%) and permeated (~45 µg/cm2) MEL amount was detected from the non-cross-linked sample. Our results indicate that spray-dried MEL-containing chitosan microparticles may be recommended for the development of a novel drug delivery system to decrease acute pain or enhance analgesia by intranasal application.